Tuberculosis in patients with systemic lupus erythematosus - Ongarj, Jomkwan; Intapiboon, Porntip; Tanner, Rachel; Pinpathomrat, Nawamin (Frontiers in Immunology, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (M. tb), with approximately 10 million new cases reported worldwide annually. Patients with immunocompromised states or those receiving immunosuppressive therapy for autoimmune diseases are at higher risk of M. tb infection or reactivation. The chronic autoimmune disease, systemic lupus erythematosus (SLE), is associated with a higher risk of M. tb infection and TB disease during conventional treatment with corticosteroids and immunosuppressants. However, whether risk of TB is influenced by the immune disturbances associated with active SLE when patients are not receiving immunosuppressant treatment remains unclear. In this review, we describe the pathogenesis of TB and SLE and consider how autoimmune responses in SLE could influence TB risk.